Academic Libraries and Athletic Departments: A Nurturing Collaboration - Jesudason, Melba (My University, 1993)
Student-athletes must meet the demands of the NCAA regulations known as Propositions 48, 42, and16 to be eligible for athletic scholarships. University libraries can develop nurturing relationships with athletic departments. This article described how College Library at the University of Wisconsin, Madison helps with recruitment of "at-risk" student-athletes through precollege outreach programs and with retention by initiating contact and by presenting library user skill modules for student-athletes.
Keywords: skills; relationship with campus; at-risk; eligibility; academic predictors